Fiscalidade e subdesenvolvimento: breves considerações sobre o Brasil independente - Scacchetti, Camila (2022)
Seeking to trace the relationship between the levels of underdevelopment and taxation, this study analyzes the fiscal construction in independent Brazil. Through the separation of revenues between the General and Provincial Coffers, Brazil witnessed a new administrative collection structure. The tithes levied on the main exported products figured as the main source of tax collection in the Provinces. However, to regions unable to fit into this dynamic, few alternatives were offered. This feat only deepened the levels of underdevelopment present in the national territory.